Fermented soybean cake nugget (tempeh) as an alternative for increasing weight of little children aged 36-60 months - B. Suriani; Jumrah Sudirman; Sitti Mukarramah; Syamsyuriyana Sabar; Hasriani Saleng (Elsevier, 2021)
Objective: This study aims to identify weight gain by giving fermented soybean cake nugget (tempeh) to underweight toddlers. Methods: This study used a quasi-experiment design with non-equivalent pre test-post test control group design. The sample was taken by using purposive sampling method. The sample size of this study was 30 toddlers. Results: Based the result of the intervention group the mean ± SD was 846.67 ± 333.524 while the control group had a value mean ± SD 326.67 ± 349.421 while p value is 0.001 < 0.05. If the p value is 0.05, there is a significant difference between the intervention group and the control group. Conclusions: Fermented soybean cake nugget provide a good weight gain effect on toddlers, therefore consumption of fermented soybean cake nugget can be recommended and taught to the public. Therefore fermented soybean cake nugget can be given to help supplement food for toddlers.